The complete mitochondrial genome sequence of Lepus tibetanus pamirensis - Wenjuan Shan; Yucong Zhang; Mayinur Tursun; Shiyu Zhou; Huiying Dai; Mireguli Maimaiti (Mitochondrial DNA. Part B. Resources, 2020)
Lepus tibetanus pamirensis distributes only in the Pamir Plateau under a harsh environment with high attitude, cold and dry climates. The complete mitochondrial genome of the hare was determined (accession number MN539746) in a total length of 16,753 bp. The overall base composition of L. t. pamirensis mitogenome is 31.6% for A, 25.7% for C, 13.3% for G and 29.5% for T. It has the common characteristic with other mammals in regard to genome structure and gene arrangement. Based on published complete mitogenome sequences of lagomorphs, the phylogenetic tree suggested that L. t. pamirensis is closely related to L. yarkandensis and has far relationship with L. capensis. Our results would provide useful information for further study on conservation genetics and evolution of this hare species.